ANALISIS FAKTOR LIFE STYLE TERHADAP RESIKO HIPERTENSI - Nurul Agustin; Ambar Asnaningsih (Jurnal Penelitian, 2022)
Hypertension is a silent killer, because it occurs without any symptoms or is asymptomatic. Hypertension can occur due to several risk factors, namely family history, poor living habits, poor dietary patterns and poor sleep quality. The purpose of this study was to analyze the effectiveness of zumba dance and aerobic exercise on controlling blood pressure which is influenced by lifestyle behavior in the community. The research design used in this study is descriptive analytic with a cross-sectional approach. This study uses Cluster Sampling with a population of 560 people. The data collection instrument used a closed questionnaire which was processed through the process of editing, coding, scoring, tabulating. After that, it was analyzed with Chi Square statistical test using SPSS. So, H1 accepte, it mean there is a relationship between nutritional status, physical activity, sleep quantity, smoking habits, consumption of coffee, and stress on the risk of hypertension.